2020
DOI: 10.3390/s20226636
|View full text |Cite
|
Sign up to set email alerts
|

Washing Machine Dynamic Model to Prevent Tub Collision during Transient State

Abstract: In horizontal-axis washing machines, the front gasket as well as the damping system are crucial owing to the possible collision of the tub with the housing during the transient period. However, most dynamic models for predicting tub motion focus on the steady state and consider only the suspension system without including the gasket. We conducted an experimental study to analyze the effect of the gasket on the transient motion of the tub. The results obtained indicate the necessity of implementing the gasket i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, there is a bit of a difference between the rest of the NFs of the X,Yand Z displacements. As noted by previous studies in the literature, it is observed that the time histories of displacements that are measured (as in experimental studies 23,24 ) or calculated (as in simulation studies 16 ) at different locations often lead to different identified values for the NFs even though the number of NFs remain the same. This difference is attributed to not selecting a most suitable measurement point.…”
Section: (B)-(d) Present the Frequency Spectrumsmentioning
confidence: 85%
“…However, there is a bit of a difference between the rest of the NFs of the X,Yand Z displacements. As noted by previous studies in the literature, it is observed that the time histories of displacements that are measured (as in experimental studies 23,24 ) or calculated (as in simulation studies 16 ) at different locations often lead to different identified values for the NFs even though the number of NFs remain the same. This difference is attributed to not selecting a most suitable measurement point.…”
Section: (B)-(d) Present the Frequency Spectrumsmentioning
confidence: 85%
“…This process will be repeated iteratively until the maximum number of iterations is reached. Finally, the optimal parameter set found by the proposed framework is the design for the washing machine, which produces the minimum displacement amplitude, i.e., Block (7) in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…One serious issue that needs to be studied is the vibration-induced walking problem that occurs when the machine operates at a high speed [5,6], which is a stability concern, produces large noise, and leads to poor energy efficiency. Another one is the collision of internal components of the washing machine during its operation, which needs to be avoided [7]. Therefore, a more stable, quiet, and light weighted washing machine is desired by customers [1].…”
Section: Introductionmentioning
confidence: 99%